PENDEKATAN KONSEPTUAL TERHADAP IMPLEMENTASI STANDAR MUTU KEKHASAN DI SDIT DARUL FURQAN PARIAMAN - Ira maya sofa; Rahayu Rahmadani; Nova Arianti; Rahma Yuni; Ramayulis Rahman; Ratna Juita; Merry Yelliza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the implementation of distinctive quality standards in Integrated Islamic Schools (JSIT) through a conceptual approach. The main focus of the research is how Islamic values are integrated in curriculum, learning, and evaluation at JSIT. The method used is a literature study, by reviewing literature related to integrative curriculum, holistic education, and value-based evaluation. The results showed that JSIT combines the national curriculum with Islamic values, creating balanced learning between cognitive, affective, and psychomotor aspects. Teachers act not only as teachers but also moral guides (murabbi), forming an environment that supports students' Islamic character. Evaluation not only measures academic achievement, but also students' character and spiritual development. This study suggests the need for continuous training for educators and further research to explore more deeply the effect of implementation on learning outcomes and student character.